Analysis of Sedimentation in the Mongiilo River Using the HEC-RAS Program: Analisis Sedimentasi di Sungai Mongiilo Menggunakan Program HEC-RAS - Indarwati, Syukron; Husnan, Rawiyah; Labdul, Barry Yusuf (Jurnal Teknik Sumber Daya Air, 2025)
The river flow that enters the dam has great potential in transporting large amounts of sediment from land erosion that occurs upstream. Sediment material that dissolves with the river flow will then settle in the dam as long as the water structure is in operation. Sedimentation occurs through the process of deposition of soil material which is transported by water or wind. Sedimentation in the riverbed are identified as the causing siltation of river body, irrigation canals, river mouths downstream, and can damage the cross section of the river and have an impact on the effective age of water buildings in the river, in this case the Bulango Ulu Dam. The research location is at the Mongiilo River, Owata Village, North Bulango District, Bone Bolango Regency. This study aims to analyze the sedimentation rate that occurs in the Mongiilo River using the HEC-RAS program. The data used in this study are primary and secondary data. The primary data used for this research was carried out by means of field surveys for sampling, while the secondary data used was obtained by means of literature review and interviews with related agencies such as the Balai Wilayah Sungai Sulawesi II. The results of the analysis in this study obtained that the sediment characteristics in Mongiilo River according to American Geophysical Union are dominated by medium sand, and the sediment transport rate obtained and close to the project data with a value of 200.674,83 tons/year which is using the Meyer-Peter Muller method is 175.484,796 tons/year.